Beakers with corded ornamentation in the Northwestern Pontic (Early Bronze Age) - Ivanova, Svitlana; Bruyako, Igor (Sprawozdania Archeologiczne, 2025)
Corded ornamentation is known on pottery from various Eneolithic and Bronze Age archaeological cultures in the Northwestern Pontic region. The ornamental patterns vary and are not associated with any particular type of vessel. This article examines beakers decorated with compositions of cord impressions. These have predominantly been found in the burials of the Budzhak/Yamna culture. Their distribution may be related to the influence of different cultural blocks – the northern block, associated with the Corded Ware culture, and the western block, linked to the cultures of the Early Bronze Age in the Balkan and Danube region.